Risk Analysis of Musculoskeletal Disorders Using RWL And LI Methods - Nuril Fahmi; Deny Andesta (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2023)
Material handling is an activity that is often carried out by everyone in daily activities, especially in activities in a company. Material transfer or material handling without the use of tools, commonly referred to as "manual material handling," can affect a production process in the company. At PT. X, there is a manual material handling activity with a total load of 23 kg, namely taking water treatment analysis samples. This study's goal is to make a recommendation for changing how employees behave at work when taking samples for water treatment analysis. In completing this study, the methods used were the Recommende Weight Limit (RWL) and Lifting Index (Li) methods. according to the results of the recommended weight limit method's calculations, the recommended load weight was obtained with an average weight of 8 kg and was known. And based on Li's calculations, the value of Li > 1 was obtained, It indicates that there is a potential of spinal injury during the activity. So it is necessary to make improvements using manual tools or layout improvements to make it more effective and efficient.